Tackling disabilities in young age: Policies that work - Kristine von Simson; Inés Hardoy (IZA Journal of Labor Policy, 2020)
Work impairment is an increasing concern in advanced economies, particularly among young people. Activation, rather than passively providing economic support, is often regarded as the preferred strategy for addressing this issue. However, little is known about which measures are effective for improving youth work impairment. A hazard rate competing risk model with unobserved heterogeneity applied to rich Norwegian panel data provides some insights. Wage subsidies, and to some extent education/training programs, have the intended effect. In other words, work-impaired youths who participate in these measures have a higher probability of obtaining work/starting an education and a lower probability of experiencing a transition to social security than those youths who do not participate in any measure. The impacts of follow-upinitiatives and work practice programs are more mixed.
Keywords: C41; I38; J08; J22; J24; J68; 330; reduced work capacity; vocational rehabilitation; Timing-of-Events model; youth